2021
DOI: 10.12968/hmed.2021.0145
|View full text |Cite
|
Sign up to set email alerts
|

Recognising and managing retinal detachments

Abstract: Retinal detachments are a potentially sight-threatening ophthalmic emergency that may result in significant, irreversible vision loss. The risk of developing retinal detachment increases with advancing age, myopia and trauma. Pre-existing retinal degenerations can precipitate a pre-detachment symptomatic period of photopsia or floaters, allowing clinicians to intervene early and prevent detachments. Novel imaging techniques, such as spectral-domain optical coherence tomography, and well-established topographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Separating chronic macula-off RD into without PVD and with a PVD has important prognostic and surgical implications. Chronic macula-off RD without PVD tends to occur in young patients and have good anatomic success when repaired by scleral buckle [5,6,10,11]. Chronic RD with PVD tends to occur in older patients with higher rates of PVR, low primary surgical success, and high rates of postoperative complications [7,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Separating chronic macula-off RD into without PVD and with a PVD has important prognostic and surgical implications. Chronic macula-off RD without PVD tends to occur in young patients and have good anatomic success when repaired by scleral buckle [5,6,10,11]. Chronic RD with PVD tends to occur in older patients with higher rates of PVR, low primary surgical success, and high rates of postoperative complications [7,15].…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of PVR are also noted in chronic macula-off RD with PVD compared to without PVD. Low rates of PVR grade C or greater have been noted in chronic macula-off RD without PVD (i.e., Yao et al reported ~ 10%) [5,6,10]. Anguita et al had rates of PVR at 69% in chronic macula-off RD with PVD [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal tears associated with head trauma may present as photopsia (Sornalingam et al, 2018). It is particularly important to assess for retinal tears and retinal detachment when evaluating head trauma because these are emergencies that require prompt intervention (Amos, 1999;Ibrar et al, 2021). Symptoms may be overlooked and attributed to the concussed state (Bedgood et al, 2015).…”
Section: Flashing Lights After Tbimentioning
confidence: 99%
“…Currently, the diagnosis of RD mainly relies on optical coherence tomography and B-scan ultrasonography; the results of these examinations can help to identify the type of RD and extent of detachment (Ibrar et al, 2021). However, such examinations only explore ocular visual function in RD patients; it has been unclear whether CNS abnormalities exist in such patients.…”
Section: Introductionmentioning
confidence: 99%